If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 7q = 15 + 16q Solving 13 + 7q = 15 + 16q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-16q' to each side of the equation. 13 + 7q + -16q = 15 + 16q + -16q Combine like terms: 7q + -16q = -9q 13 + -9q = 15 + 16q + -16q Combine like terms: 16q + -16q = 0 13 + -9q = 15 + 0 13 + -9q = 15 Add '-13' to each side of the equation. 13 + -13 + -9q = 15 + -13 Combine like terms: 13 + -13 = 0 0 + -9q = 15 + -13 -9q = 15 + -13 Combine like terms: 15 + -13 = 2 -9q = 2 Divide each side by '-9'. q = -0.2222222222 Simplifying q = -0.2222222222
| 25=5(8x+5)+2x | | 5x-1*2=7 | | a*3+7=14 | | x^2-90x+225=0 | | x^2+28x-104=0 | | 11q+8q=16+7q | | (4x+9)(x-6)=0 | | X+2=5(x-2) | | 8(5v+3)=-56 | | y=2x^3-24x-2 | | x*8=2.25 | | (x-8)(x-1.67)=0 | | 7-3/m18/m | | -60=-6(4b+2) | | 6(-9+7x)=-306 | | -2(8+x)=-12 | | -2(8+n)=-10 | | (3x-6)+2(2x-5)=26 | | 64+64+x+x=180 | | 5(m+9)-8(12-m)= | | 3(7x+7)=189 | | 8x-16=9x+8 | | 3x+2=x+40 | | 3(3-6x)=-117 | | -1=-(1-4x)+x | | 6(4x+10)=324 | | 3x+15x+150=0 | | 9/2a-5=-1 | | 18-(x+3)-2x=4+(x-5) | | 7+7x=3x+47 | | 5+(-15d+1)=2(7d-16)-d | | -4+p=-2 |